Studying Proteus mirabilis Typing Isolated from Urinary Tract infections (Baghdad Science Journal, 2012)
Urine specimen (253 samples) had been collected from urinary tract infections. The study showed that Proteus mirabilis was responsible for (11.85%) of the urinary tract infections. Also, the study had declared that the ratio of isolation of this bacterium from women was (7.51%) and it was higher than the ratio in both men and children which ranged (1.58%) and (2.76%) respectively. Morphological and biochemical studies had been applied to characterize this bacterium as well as other kinds of microorganisms that were isolated from urinary tract infection in this study. The study deals with typing methods such as using biotyping and typing according to Dienes phenomenon beside the succestibility to antibiotics. The results had shown that the second biotype B.T.2, the third type of Dienes phenomenon D.3 and sixth sensitive type S.3 were most familiar in causing urinary tract infections, while the third biotype was recorded as a new biotype in this study. The study was considered as a first local study that deals with Dienes phenomenon and using it in typing of this bacterium.